Pengembangan Danau Bulat Sebagai Destinasi Wisata Di Kabupaten Katingan Provinsi Kalimantan Tengah: The Development Of Round Lake As A Tourist Destination In Katingan District Central Kalimantan Province - Jariah, Ainun (Pencerah Publik, 2019)
This research aims to determine the development of Round Lake as a tourist destination in Katingan district, Kalimantan Central province and its termination factor. This research uses a qualitative method that aims to find the meaning of a phenomenon in the background of a specific context and analyzed the reduction technique that is then presented sera done draw conclusions. The results of the research on the development of the Round Lake tourism destination in the Katingan regency of central Kalimantan province can be concluded that 1) has not been carried out marketing research in policymaking and program 2) innovation made Yet effective, thus demanding innovations in the field of development and marketing 3) still a mini chance for the community to engage in the development of around Lake tour. The inhibiting factor in the development is that the accessibility available is sufficient enough but the traveled distance is quite time-consuming and the road is passed perforated. Also, facilities and infrastructures that support the gate or post are not yet available, the direction to which the tourist destination also does not exist. Another factor is the data information system that belongs to the tourist destination and Aubulat is also quite minimal. The potentials that have not yet been once can be developed. This is because the community will be able to expand the tourism destination of the Round lake by the wishes.